Energy : readings from Scientific American - Singer, S. Fred (Siegfried Fred), 1924- (San Francisco : W. H. Freeman & Company, 1979)
Energy and power--The Conversion of energy--The Economic geography of energy --Oil and gas from coal--The Stripmining of Western coal--The Necessity of fission power--(etc.).
Includes index.
Bibliography: p. [215]-218.
Young Adult.
Young Adult
Keywords: Power (Mechanics); Power resources